POLITICAL CRISIS, MEDIA AND EMOTIONS - Serafimovska, Eleonora; Markovikj, Marijana; Trajkov, Ivan (INSTITUTE FOR SOCIOLOGICAL, POLITICAL AND JURIDICAL RESEARCH UNIVERSITY “Ss. CIRYL AND METHODIUS” - SKOPJE, 2016)
Macedonia will remember 2015 as a year of long-term political crisis. It was a year of intensive activity against the Government. There were “opposition bombs”, disclosed incriminating phone calls, strikes in education, mass protests, camping in front of the Government and the Assembly, a police action against the terrorists in Kumanovo, migrant crisis .... The understanding of the start and the end points of the crisis largely depends on the individual perception created as a result of the personal experience and the experience mediated through offline networks, online networks and media. Apart from the diversity of the events in the surroundings there is also a difference in the style of processing or living one’s own emotions (feeling them, expressing them, understanding them). This research focusses on how students process emotions provoked by news/media stories on the events connected to the abovementioned critical political events. Students from the Faculty of Philosophy, University “Ss. Cyril and Methodius” voluntarily accepted to take part in this research. Two research instruments were used: questionnaire for the evaluation of the media content and their influence on the emotions of the respondent and the Emotional Processing Scale (EPS) regarding the nature of processing emotions. The research design provides quantitative and qualitative analysis. This study showed that anger, fear and rage are dominantly provoked by negative emotions which are unprocessed or there is avoidance of coping with them (the two unhealthy ways of emotional processing).
Keywords: Political crisis, Media and emotions, Emotional processing, Media stress, Emotional processing scale